ANALYSIS OF THE PHD PROGRAMME DEVELOPMENT IN KAZAKHSTAN - Asanova D. (Хабаршы. Заң сериясы, 2018)
Since 1993, the higher and postgraduate education management system in Kazakhstan has gone through systemic modernization that was determined by the economic and political development of the sovereign state, its accession into the global market, and growth of competitiveness of its human capital. For a quarter of the century, a new methodological approach to education has been formulated and is being introduced – lifelong learning –, that reflects the fundamental principles of the Bologna Conven-tion. The Republic of Kazakhstan was one of the first countries in the former Soviet Union to introduce a credit system of education and moved to a three-level system of personnel training: higher graduate education – bachelor’s degree, post-graduate education – master’s degree, doctorate – Doctor of Phi-losophy. In this regard, fundamental changes were made, and a new model of doctors of philosophy (PhD) training was created. A key element in the framework of a three-stage training system is a PhD program, because of their status is intended to develop scientific schools, set the trend of science and innovation, advance scientific ideas and hypotheses, and generally ensure the development of a national model of the country’s innovation economy. This analytical review is devoted to topical issues of doctors of philosophy (PhD) training and to identify ways of improving postgraduate education in Kazakhstan.